2020
DOI: 10.1111/imj.14686
|View full text |Cite
|
Sign up to set email alerts
|

Hospital infection control: old problem – evolving challenges

Abstract: Hospital infection prevention and control (IPC) is often regarded by doctors as mundane and unnecessarily rigid, but the continued occurrence of preventable healthcareassociated infections, increasing antimicrobial resistance (to which hospitals are major contributors) and rare, but potentially devastating hospital outbreaks of emerging infectious diseases, suggest that IPC must be taken seriously. Healthcare professionals often fail to comply with effective, evidence-based IPC practices and there is ample evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A study that explored ICU nurses' experiences of infection control guidelines in emergency situations (Donati et al, 2019) found that nurses only partially implemented infection control guidelines, and debated whether they should follow strict infection control guidelines or respond to the emergency when they did not have enough time. According to a study on the infection prevention guidelines performance of physicians (Gilbert & Kerridge, 2020), lack of adherence to infection control was widespread and consistent across all healthcare professionals including physicians; the study presented various reasons including lack of role models, excessive workload, focusing on immediate patient treatment, inconvenience of using personal protective equipment, uncertainties with policy application, and unclear penalties for non‐compliance. Such a poor infection control performance ultimately threatens patient safety and even healthcare professionals themselves (Donati et al, 2019); it is critical to follow guidelines and accurately implement infection control despite its time‐consuming nature and healthcare workers' busy schedules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that explored ICU nurses' experiences of infection control guidelines in emergency situations (Donati et al, 2019) found that nurses only partially implemented infection control guidelines, and debated whether they should follow strict infection control guidelines or respond to the emergency when they did not have enough time. According to a study on the infection prevention guidelines performance of physicians (Gilbert & Kerridge, 2020), lack of adherence to infection control was widespread and consistent across all healthcare professionals including physicians; the study presented various reasons including lack of role models, excessive workload, focusing on immediate patient treatment, inconvenience of using personal protective equipment, uncertainties with policy application, and unclear penalties for non‐compliance. Such a poor infection control performance ultimately threatens patient safety and even healthcare professionals themselves (Donati et al, 2019); it is critical to follow guidelines and accurately implement infection control despite its time‐consuming nature and healthcare workers' busy schedules.…”
Section: Discussionmentioning
confidence: 99%
“…However, some inconsistent results have been reported, for example, nurses' education, clinical experience, and safety education did not influence patient safety (Yang, 2019), and nurse‐to‐patient ratio and patient outcomes were not related (Verbeek‐Van Noord, Wagner, Van Dyck, Twisk, & De Bruijne, 2014). Moreover, even physicians and nurses do not implement infection control measures despite knowing about them in emergency situations in the emergency room and ICU (Donati et al, 2019; Gilbert & Kerridge, 2020). In summary, it is important to consider how patient safety can be influenced by organizational staffing levels, as well as nurses' individual knowledge, practice, and experience despite the organization's infection control discipline and culture.…”
Section: Introductionmentioning
confidence: 99%
“…As Winton(D) astutely observed, and has been recognised elsewhere (Cabana et al, 1999), the ability to overcome the inertia of previous practice is a common reason for noncompliance. Doctors may demonstrate outright hostility towards guidance that they see as an imposed device of managerial control rather than an intrinsic part of patient care (Gilbert & Kerridge, 2020).…”
Section: Cultural Norms Attitudes and Beliefsmentioning
confidence: 99%
“…The reviewers (M.A.A. 1 , A.R.M., and M.A.A. 2 ) retrieved data on study design, population and setting, and the positive deviance intervention definition using paperbased forms.…”
Section: Data Abstraction and Quality Assessmentmentioning
confidence: 99%
“…Healthcare-associated infections (HAIs) remain a major challenge 1,2 ; they are associated with increased morbidity and mortality. 3 The total annual cost for the major HAIs is ~$10 billion in the United States.…”
Section: Introductionmentioning
confidence: 99%